Current knowledge of leptin in wound healing: A collaborative review - Yuan, Chi; Liao, Jian; Zheng, Liying; Ding, Lingzhi; Teng, Xiao; Lin, Xuesong; Wang, Le (Frontiers in Pharmacology, 2022)
Efficacious wound healing is still a major concern for global healthcare due to the unsatisfactory outcomes under the current treatments. Leptin, an adipocyte-derived hormone, mainly acts in the hypothalamus and plays crucial roles in various biological processes. Recently, an increasing number of researches have shown that leptin played an important role in the wound healing process. In this review, we presented a first attempt to capture the current knowledge on the association between leptin and wound healing. After a comprehensive review, the molecular mechanisms underlying leptin in wound healing were speculated to be correlated to the regulation of inflammation of the macrophage and lymphocytes, angiogenesis, re-epithelialization, proliferation, and differentiation of fibroblasts. The affected genes and the signal pathways included ERK-1, MAPK, JAK-2, STAT1/3, hBD-2, Akt, COX-2, VEGF, FGF-2, and NF-κB cascades. However, the understanding of the specific role in each process (e.g. inflammatory, proliferative, and maturation phase) of wound repair is not entirely clear, and further studies are still warranted in both macrostructural and microscale factors. Therefore, identifying and validating the biological mechanisms of leptin in wound healing is of great significance to develop potential therapeutic targets for the treatment of wound healing in clinical practice.